Prevalence of type 2 diabetes mellitus among non teaching staff of a medical college in North Karnataka: a cross sectional study - Yadav, Birendra Babu; S., Shivaswamy M.; Mallapur, M. D. (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes threatens to assume pandemic level by 2030 and there is no available statistics of type2 diabetes mellitus on non-teaching staff. The risk factors like bad habits, family history, waist hip ratio (≥ 0.9 in males and ≥0.85 in females), BMI (≥28) and IDRS (>60) all attributed to the high prevalence of pre-diabetic as well as diabetes. Aims: To know the prevalence of Type 2 Diabetes Mellitus among non-teaching staff and to determine the risk factors associated with it. Methods: A facility based cross – sectional study was conducted among all the non-teaching staff of Jawaharlal Nehru Medical College, Belagavi from February to October 2014.A total 500 (394 males and 106 female) participants between age group 20-59 years were selected for the study. After taking written informed consent, information regarding socioeconomic and risk factors were collected though pre – tested questionnaire. Physical examination were done to calculate BMI, Waist –Hip ratio and IDRS (Indian diabetes risk score). The random blood sugar was estimated to identify the diabetes and pre-diabetics. Results: The overall prevalence of diabetics and pre- diabetics was 5 per cent and 17 per cent respectively. The prevalence of diabetes was highest in age group 50-59 years. The risk factor like bad habit, waist hip ratio (≥0.9 in males and ≥0.85 in females), BMI (≥28) and IDRS (>60) attributed to high prevalence of pre diabetics and diabetics. Conclusions: The prevalence of diabetes was more among non-teaching staff so; both preventive and curative services should be provided to them.